Graph wavelet transform for image texture classification. Issue 10 (16th April 2021) - Qiao, Yu‐Long; Zhao, Yue; Song, Chun‐Yan; Zhang, Kai‐Ge; Xiang, Xue‐Zhi
Abstract: Graph is a data structure that can represent complex relationships among data. Graph signal processing, unlike traditional signal processing, explicitly considers the structure and relationship among the signal samples. Graph wavelet transform can provide a multiscale analysis for the graph signal. It is well known that texture is a region property in an image, which is characterized with the intensity and relationship among pixels. In this context of the graph signal processing framework, an image texture can be considered as the signal on the graph. Therefore, a texture classification method based on graph wavelet transform is proposed. Specifically, image textures are decomposed into multiscale components by using two‐channel graph wavelet filter banks. Then the local singular value decomposition is applied to each subband. In order to improve the noise‐resistant ability, the maximum, mean and median values of the local singular values of graph‐wavelet transformation coefficients are extracted. Finally, the Weibull distributions are used to model those extracted values to describe the image textures. The experiments on the benchmark texture datasets are conducted to demonstrate the effectiveness of the proposed method.